Effectiveness of principals exemplary leadership practiced on school achievements:stakeholders’ perceptions - Salleh, Mohamad Johdi; Khalid, Robita (Open Access Publishing Group, 2018)
The study examines the effectiveness of principals’ exemplary leadership practiced on school achievements as perceived by stakeholders. The respondents were 193 stakeholders comprised Senior Assistants, Afternoon session School Supervisors, Officers of District Education Office, teachers, and, representatives of Parent Teacher Association. The study adapted the Leadership Practices Inventory (LPI) model developed by Kouzes and Posner (2001, 2004). The data collected from the survey were analysed using a statistical software package, Statistical Package for Social Science (SPSS) version 23.0. The results showed that the component ‘Enable Others to Act’ was the most effective practiced with the highest mean score of 4.12 and standard deviation 0.700. The second highest was ‘Challenge the Process’ with mean 4.01 and standard deviation 0.764. The third highest was ‘Encourages the Heart’ with mean 4.00 and standard deviation 0.771. It was followed by ‘Inspired a Shared Vision’ with mean 3.97 and standard deviation 0.739. On the other hand, the stakeholders have identified the lowest score was the component ‘Model of the Way’ with mean 3.77 and standard deviation 0.768. It is hoped that this study would effectively benefit leaders and educators in schools towards realization of the Malaysian Education Development Plan 2013-2025.